Phylogeny of pentatomomorphan bugs (Hemiptera-Heteroptera: Pentatomomorpha) based on six Hox gene fragments - Tian, Xiaoxuan; Xie, Qiang; Li, Min; Gao, Cuiqing; Cui, Ying; Xi, Li; Bu, Wenjun (Zootaxa, 2011)
Pentatomomorpha is one of the most diversified infraorders of the true bugs (Insecta: Hemiptera: Heteroptera). The phylogenetic relationships among superfamilies within this infraorder are still in dispute. In this study, 31 species representing 26 pentatomomorphan and four cimicomorphan putative families were chosen, and six Hox gene fragments with as many as 4 kilobases for each representative were analyzed to reconstruct the phylogeny of the Pentatomomorpha. The (Homeotic) Hox gene family is a group of nuclear genes, which is considered to determine animal segmentation. The combined nucleotide and amino acid sequences were used separately as two data matrices, and analyzed by employing maximum likelihood and Bayesian methods. Results strongly support the monophyly of Trichophora and the superfamilies Pentatomoidea, Lygaeoidea, Coreoidea, and Pyrrhocoroidea. The relationship of (Aradoidea + (Pentatomoidea + (Lygaeoidea + (Coreoidea + Pyrrhocoroidea)))) was mostly congruent with previous results based on the morphological data. Our results suggested that the Hox genes could be used as novel molecular markers for phylogenetic research on the Pentatomomorpha and other insects.